The Influence Of Halal Logos, Religiosity, And Knowledge About Halal On Buying Interest In Ice Cream Products From China. - Faizah, Nilna; Farisi, Herdian; Sukoco, Hendro (Business Finance Analyst Co., 2024)
The purpose of this study was to determine the effect of halal logo, religiosity, halal knowledge on buying interest in ice cream products from China, namely Mixue. The study employed quantitative methods with purposive sampling. It gathered primary data through surveying 100 Mixue consumers in Purwokerto. Statistical analysis using multiple linear regression revealed that the presence of a halal certification significantly increases purchase intent. However, religious commitment and knowledge about halal products did not show a significant influence on Mixue's purchase intention in Purwokerto. This study aims to provide valuable insights for Mixue's operations in Purwokerto and other related parties regarding what halal logo, religiosity, and halal knowledge are most attractive to Mixue consumers in Purwokerto city.